2013
DOI: 10.1103/physreve.88.032913
|View full text |Cite|
|
Sign up to set email alerts
|

Time fluctuations in isolated quantum systems of interacting particles

Abstract: Numerically, we study the time fluctuations of few-body observables after relaxation in isolated dynamical quantum systems of interacting particles. Our results suggest that they decay exponentially with system size in both regimes, integrable and chaotic. The integrable systems considered are solvable with the Bethe ansatz and have a highly nondegenerate spectrum. This is in contrast with integrable Hamiltonians mappable to noninteracting ones. We show that the coefficient of the exponential decay depends on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 60 publications
4
68
0
1
Order By: Relevance
“…In systems without an excessive number of degeneracies and for initial states away from the edges of the spectrum, in other words when |k 0 has a chaotic structure, the temporal fluctuations decrease exponentially with the system size [219]. It has been shown that this holds not only for models with a Wigner-Dyson level spacing distribution, but also for integrable models with interaction, such as Model 1.…”
Section: Relaxation Of Few-body Observablesmentioning
confidence: 94%
See 1 more Smart Citation
“…In systems without an excessive number of degeneracies and for initial states away from the edges of the spectrum, in other words when |k 0 has a chaotic structure, the temporal fluctuations decrease exponentially with the system size [219]. It has been shown that this holds not only for models with a Wigner-Dyson level spacing distribution, but also for integrable models with interaction, such as Model 1.…”
Section: Relaxation Of Few-body Observablesmentioning
confidence: 94%
“…Systems that fall in this category are those without level clustering [219]. They include chaotic models and those with the Poisson level spacing distribution, known to be a fingerprint of integrable systems, but obviously exclude systems characterized by a picket fence spectrum.…”
mentioning
confidence: 99%
“…In the absence of disorder, the envelope ρ n 0 (E) is particularly well filled for initial states with energy ε n 0 near the center of the spectrum of H [56,57]. Its Gaussian shape leads to the Gaussian decay F (t) ∼ exp(−σ 2 n 0 t 2 ).…”
Section: Survival Probabilitymentioning
confidence: 99%
“…(iii) When the Ising interaction is present, we use = 0.48. This is sufficiently away from the midpoint = 1 2 , where the system develops additional nontrivial symmetries (see references in [55]), and it prevents conservation of total spin S 2 = ( L i=1 S i ) 2 , which happens at = 1. (iv) To avoid reflection symmetry, we add a small impurity of amplitude εJ on the first site of the chain.…”
Section: System Models and Quenchesmentioning
confidence: 99%